English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-10-05 11:36:55 · 3 answers · asked by . 1 in Science & Mathematics Mathematics

3 answers

(x-2)(x+2)(x^2+9)

2007-10-05 11:40:43 · answer #1 · answered by programhelp 2 · 0 0

call u = x^2.

Rewrite as

u^2 + 5u - 36 = (u -4 )(u + 9 ), back to u = x^2 or
= (x^2 - 4) (x^2 + 9), continue factoring
= (x+2)(x-2)(x^2 + 9). Done.

Note, there is no formula for the sum of squares.

2007-10-05 18:40:48 · answer #2 · answered by pbb1001 5 · 0 0

= (X^2 - 4)(X^2 +9)
= (X + 2)(X - 2)(X^2 + 9)

2007-10-05 18:41:29 · answer #3 · answered by norman 7 · 0 0

fedest.com, questions and answers